Characterization of activated charcoal microstructure porosity of cashewnut shell (Anacardium occidentale L.) - Dewi Alimah (Jurnal GALAM, 2021)
ABSTRACTCashew nut (Anacardium occidentale L.) shell is abundantly available as waste from chasew nut processing industries. Cashew nut shell is potentially used for activated charcoal. This paper characterize the porosity microstructure of activated charcoal made from cashew nut shells which is physically activated at various activation temperatures. Initially, cashew nut shells were collected and carbonized at 500°C for 3 hours. Then, the charcoal was activated at 800°C and 1000°C for 60 minutes. The characterization of microstructure porosity of cashew nut shell activated charcoal at transverse cross-section was carried out at 500 times magnification of 10 kV Scanning Electron Microscope (SEM) using a grain-shaped test sample. Observation of the porosity formed on the sample surface included pore size and frequency. Observation data were arranged in tabulated form and analyzed descriptively. The results showed that the frequency of pores in charcoal activated at 1000°C tended to be higher than that of charcoal activated at 800°C. The higher activation temperature increased the pore diameter of the charcoal and decreased the clogging residue.Keywords: mesoporous, pyrolysis, hydrocarbon